Association of serum uric acid level with coronary artery stenosis severity in Korean end-stage renal disease patients - Hye Yun Jeong; Hye Jeong Cho; Sang Hoon Kim; Jun Chul Kim; Mi Jung Lee; Dong Ho Yang; So-Young Lee (The Korean Society of Nephrology, 2017)
Background: Hyperuricemia is common in end-stage renal disease (ESRD) patients, and many previous studies have reported the associations between hyperuricemia and adverse cardiovascular outcomes, which are the major cause of death in such patients. We investigated the relationship between serum uric acid level and the severity of coronary stenosis in ESRD patients on maintenance hemodialysis (MHD). Methods: Among 721 patients who started MHD treatment, 102 underwent coronary angiographic tests complaining of chest discomfort that was new at initiation of MHD. We collected data on uric acid level and coronary artery luminal diameter, defining luminal diameter narrowing of more than 50% in any major coronary artery as critical-stenosis. Results: We detected critical coronary artery stenosis in 52 (57.8%) patients. The mean uric acid level was 6.6 ± 2.2 mg/dL, and that was significantly higher in the critical-stenosis group (4.9 ± 1.4 mg/dL vs. 7.8 ± 2.0 mg/dL, P < 0.001). The only independent predictor of critical-stenosis in multivariate analysis was serum uric acid level (P < 0.001). Conclusion: High serum uric acid was associated with severe coronary artery stenosis in Korean ESRD patients. Hyperuricemia is a readily modifiable factor, and appropriately preventing it could provide significant benefits in ESRD patients.